COVID-19 Recurrence Without Seroconversion in a Patient With Mannose-Binding Lectin Deficiency. (June 2021) - Hayes, Breanne; Stanley, Jonathan; Peppers, Brian P.
Introduction: The SARS-CoV-2 virus has infected more than 63, 000, 000 people worldwide after emerging from Wuhan, China in December 2019. This outbreak was declared a Public Health Emergency in January 2020, and a pandemic in March. While rare, reinfection with the virus has been reported on multiple occasions. Case Presentation: We present a case report of an individual with mannose binding lectin deficiency who tested positive on two separate occasions, months apart, and did not develop IgG antibodies to SARS-CoV-2. This patient Is a 30- year-old female healthcare worker with a past medical history of ITP, pancreatitis, GERD, anxiety and recurrent pneumonia. She presented in March 2020 with fever, nasal congestion, and dry cough. She was diagnosed with COVID-19 in March 2020, via PCR through employee health. She was treated with a course azithromycin and hydroxychloroquine. Symptoms resolved, however in June 2020, SARS-CoV-2 IgG antibodies were negative. Seven months later in October, she once again developed symptoms which were milder. She was found to have a decreased level of mannose binding lectin, normal immunoglobulin levels, and normal streptococcus pneumonia IgG antibodies. On immune work-up after recovery, she was found to have a decreased level of mannose binding lectin (<50 ng/mL), normal immunoglobulin levels, and protective Streptococcus pneumoniae IgG antibodies with appropriate vaccine response. Her SARS-CoV-2 IgG returned back as positive 8 weeks after her second infection. Discussion: This case illustrates that patients with mannose binding lectin deficiency may be at greater risk of re-infection than the general population.